The concept of matrimonial property: Conditions and regulations - Mohamed, Walid Mohamed Abdelrahman; Halim, Muhamad Mustakim Abdul (Linguistics and Culture Review, 2021)
This research paper, titled “The concept of matrimonial property: conditions and regulations” aims at identifying the definition of matrimonial property, and the stance of Shariah on it, and illustrating its terms and conditions. The significance of the paper lies in its investigation of an issue that preoccupies the public in Islamic communities, that is the issue of matrimonial property and the entitlement of either spouse to such property which they both shared in accruing. The study shall draw on an inductive analytical approach, which is based on gathering facts, and comparing and analyzing them, to produce correct scientific results.